2010
DOI: 10.1021/nn102738c
|View full text |Cite
|
Sign up to set email alerts
|

Thin Films of Functionalized Multiwalled Carbon Nanotubes as Suitable Scaffold Materials for Stem Cells Proliferation and Bone Formation

Abstract: In the field of regenerative medicine, human mesenchymal stem cells envisage extremely promising applications, due to their ability to differentiate into a wide range of connective tissue species on the basis of the substrate on which they grow. For the first time ever reported, we investigated the effects of a thin film of pegylated multiwalled carbon nanotubes spray dried onto preheated coverslips in terms of their ability to influence human mesenchymal stem cells' proliferation, morphology, and final differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(109 citation statements)
references
References 42 publications
5
102
0
Order By: Relevance
“…On the contrary, cells on the MWCNT-COOH substrates showed slightly irregular shapes, suggesting poor adherence to the substrate and thus lower cell growth (cell viability about 75%). 31 This is in agreement with an experiment by Liu et al 59 in which carboxylated SWCNTs and MWCNTs inhibited cell proliferation and osteogenic differentiation of human mesenchymal stem cells, consequently demonstrating the potential cytotoxicity of carboxylated carbon nanotubes.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, cells on the MWCNT-COOH substrates showed slightly irregular shapes, suggesting poor adherence to the substrate and thus lower cell growth (cell viability about 75%). 31 This is in agreement with an experiment by Liu et al 59 in which carboxylated SWCNTs and MWCNTs inhibited cell proliferation and osteogenic differentiation of human mesenchymal stem cells, consequently demonstrating the potential cytotoxicity of carboxylated carbon nanotubes.…”
supporting
confidence: 91%
“…42 Carbon nanotubes, with their unique physical and chemical properties are emerging as versatile tools in nanomedicine. 31,[55][56][57] It is widely known that the extracellular matrix can exert highly complex biochemical effects in a manner similar to that of growth factors (eg, BMP2), 58 resulting in dramatic changes to cell phenotypes. In this context, Nayak et al conducted a study to research whether and how polyethylene glycol (PEG)-conjugated multiwalled carbon nanotubes (MWCNTs) can, as a composite biomaterial, promote osteogenic differentiation of human mesenchymal stem cells and simultaneous bone matrix mineralization in the absence of any biochemical inducer.…”
mentioning
confidence: 99%
“…Although this observation differs from previous reports, 28,29 it was in line with our previous research on osteosarcoma rat cells, 17 and could explain why SEM analysis -which indirectly revealed distinct levels of adhesion of these progenitors for the selected substrates -failed for similar types of MWCNT scaffolds constructed by other research groups. 19 Although we did not further investigate this matter, our observations may be the basis for further exploration into the study of the molecules mediating this difference in cell adhesion.…”
mentioning
confidence: 92%
“…Using these three criteria, we and others have shown that high-purity CNT preparations sprayed on glass surfaces sustained bone cell proliferation as well as electrical activities underlying osteoblast secretory functions and matrix mineralization. [17][18][19] In addition, in closely related bioengineering fields, chemically modified CNTs alone or in combination with distinct composite materials have been applied to facilitate neuronal growth, cartilage, and myocardial tissue differentiation, among other applications. [20][21][22][23][24][25][26][27][28][29][30][31][32] Furthermore, CNTs in suspension have also been investigated as potential carriers for drug delivery, and have been shown to have no effect on vital functions of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Given the properties of biocompatibility and biodegradability of the nanoparticles, many studies now exist on the use of nanomaterials to prolong the expression of proteins for improved angiogenesis and recruitment of stem cells for tissue and organ regeneration (i.e., cardiac and vascular tissues [57,58]). Among the others, carbon nanotubes (CNTs), PEGylated multi walled carbon nanotubes (MWCNTs) [59], chitosan nanoparticles (CSNPs) [60], poly(lactic-co-glycolic acid) (PLGA) scaffolds [61], polycaprolactones (PCL) scaffolds [62], poly-L-lactic acid (PLLA) [63], polyethyleneimine (PEI) have been already explored [64].…”
Section: S15mentioning
confidence: 99%